2017
DOI: 10.1007/s00726-017-2407-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved positron emission tomography imaging of glioblastoma cancer using novel 68Ga-labeled peptides targeting the urokinase-type plasminogen activator receptor (uPAR)

Abstract: The urokinase-type plasminogen activator receptor (uPAR) is overexpressed in several cancers including glioblastoma (GBM) and is an established biomarker for metastatic potential. The uPAR-targeting peptide AE105-NH (Ac-Asp-Cha-Phe-(D)Ser-(D)Arg-Tyr-Leu-Trp-Ser-CONH) is a promising candidate for non-invasive positron emission tomography (PET) imaging of uPAR. Despite the optimal physical properties of Ga for peptide-based PET imaging, low tumor uptakes have previously been reported usingGa-labeled AE105-NH-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…AE105mut is used as negative control, and AE105 is used as positive control. The conjugation of the large chelators, NOTA or RESCA1, to the small uPAR-targeting 9-mer AE105 has as expected, a penalty on the binding to uPAR, but the interactions are still in the low nM range (15,16).…”
Section: Resultsmentioning
confidence: 56%
“…AE105mut is used as negative control, and AE105 is used as positive control. The conjugation of the large chelators, NOTA or RESCA1, to the small uPAR-targeting 9-mer AE105 has as expected, a penalty on the binding to uPAR, but the interactions are still in the low nM range (15,16).…”
Section: Resultsmentioning
confidence: 56%
“…2d and S13 † ). Briefly, CHS2 was then incubated with 68 Ga [2 mCi] under mild conditions for 15 min according to a previously reported method, 41 and purified by RP-HPLC resulting in over 95% purity (Fig. S14 † ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, three genes (PLAUR, ITGA5, and FMOD) were finally identified to be key hub genes through construction of a PPI network and screening hub genes with Cytoscape software. PLAUR, which is also known as CD87, UPAR, URKR, and U-PAR, is found to be overexpressed in multiple cancers including GBM, and contributes to tumor angiogenesis, cell migration, and invasion (Raghu et al, 2011;Raghu et al, 2012;Schuler et al, 2012;Hu et al, 2015;Loft et al, 2017). It encodes urokinase-type plasminogen activator receptor (uPAR), a GPI-anchored cell membrane receptor, which could bind with urokinase (uPA) and stimulate the intracellular signals associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%